1986
DOI: 10.2307/2328238
|View full text |Cite
|
Sign up to set email alerts
|

Callable Bonds: A Risk-Reducing Signalling Mechanism

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.251.160 on Tue ABSTRACTThe theory of financial economics has failed to distinguish advantages of callable bonds from those of short-term de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 10 publications
1
37
1
1
Order By: Relevance
“…We also find that most of the positive reaction to debt announcements occurs in response to short‐term debt announcements. This runs contrary to the predictions of the Robbins and Schatzberg [17] signalling model but is strongly suggestive of the type of signalling found in Flannery [7] and Slovin and Young [20]. A cross‐sectional analysis revealed that the magnitude of the reaction was not influenced by type of REIT (mortgage or equity), time period, or level of net operating income.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…We also find that most of the positive reaction to debt announcements occurs in response to short‐term debt announcements. This runs contrary to the predictions of the Robbins and Schatzberg [17] signalling model but is strongly suggestive of the type of signalling found in Flannery [7] and Slovin and Young [20]. A cross‐sectional analysis revealed that the magnitude of the reaction was not influenced by type of REIT (mortgage or equity), time period, or level of net operating income.…”
Section: Discussioncontrasting
confidence: 78%
“…In this section, we test two signalling models. The model of Robbins and Schatzberg (R‐S) [17] suggests that (a) short‐term debt and long‐term callable bonds both dominate long‐term noncallable bonds as a signalling mechanism and (b) risk‐averse managers will prefer long‐term callable bonds over short‐term debt. A test of their model can be undertaken by examining subsets of our debtissuance sample.…”
Section: Additional Findingsmentioning
confidence: 99%
“…Alternatively, firms with more free cash flows can easily divert their cash flow from investing in traditional/safer projects to riskier opportunities. Barnea, Haugena, and Senbet (1980) and Robbins and Schatzberg (1986) investigate the use of call provisions in resolving information asymmetry problems. In their models, management possesses positive private information that cannot be credibly revealed to outside investors.…”
Section: Previous Researchmentioning
confidence: 99%
“…We use a stylized model as in Robbins and Schatzberg (1986) that builds on the basic framework from Harris and Raviv (1985). Our model uses a nonzero call price and a call notice period.…”
Section: The Modelmentioning
confidence: 99%
“…This terminal cash flow can take on one of two values, namely e = H (high value) or f = M (low value). In our stylized model (see Robbins & Schatzberg, 1986), firm value, v, is assumed to evolve according to the process shown in Figure 1. Specifically, we assume that the probability of being on the upper arm (equivalent to getting closer to the "high" state), y, is such that the expected firm value at time t = 0 satisfies E o ( v l F ) > E , ( e I B ) , and that y I 1 .…”
Section: The Modelmentioning
confidence: 99%